(untitled) (Orinoquia, 2016)
Due to the rapid growth of the fetus it is particularly vulnerable to insults and changes in hormonal milieu. Therefore, is suggested that adverse situations experienced by the pregnant mother can alter the development and health of offspring, mainly due to the permeability of the placental barrier to various hormones and substances. The aim of the present investigation was to study the effects of prenatal stress in the regulation of pulmonary allergic inflammation, employing the murine model of experimental asthma. For this purpose, were used virgin female mice, Swiss lineage, of 50 days old. The models used were foot shock to induce prenatally stress, and "New York subway" stress to induce postnatally stress. Females were divided into 4 groups: CC group: not stressed females; CE group: postnatally stressed females (PND60); EC: females born from stressed mothers (GD15 to GD18); EE Group: females born from stressed mothers (GD15 to GD18) (footshock) and postnatally stressed (PND60). The induction of allergic pulmonary inflammation was done through sensitization of animals with 0,1 mg.Kg-1 sc of ovalbumin (OVA) solution, to further evaluate leukogram, bronchoalveolar lavage (BAL) hematopoietic marrow cellularity and neurochemistry. The experiments were performed 24 hours after the last session of nebulization. The number of BAL cells was significantly higher in EE group animals compared with the CC group (P<0.01), CE (P<0.01) and CE (P<0.001). In the differential count of the BAL, lymphocytes and macrophages of EE group were significantly higher than the other groups studied (P<0.05). In the blood differential cell count were not observed changes (P>0.05) for lymphocytes, neutrophils, eosinophils and monocytes; however, there were significant differences (P<0.05) observed in the number of rods cells between groups, being higher in animals the CC group compared to EC group. The number of hematopoietic cells of the bone marrow was significantly lower (P<0.05) in animals of Group EE, compared with CC group. In the prefrontal cortex, there were significant differences in homovanillic acid /dopamine (HVA/DA) (P<0.05) rate, being higher in the EC group, compared to EC group. In conclusion, prenatal stress modulated the immune system (SI) cells of neonates, evidenced after exposure to a post-natal acute stress by amplification of pulmonary allergic response. It is suggested that the increased susceptibility of animals EE group is a result of changes induced by prenatal stress on hypothalamus pituitary-adrenal (HPA) axis.